ANALISIS POTENSI SEKTOR POTENSI PERTANIAN DI KABUPATEN KEDIRI TAHUN 2010-2014 - Rasyid, Abdurrahman (Jurnal Ekonomi Pembangunan, 2016)
The purpose of this study refers to the content and formulation of research problems, namely: to identify the structure of the economy in Kediri, analyzing knowing what economic sectors into competitive advantage and specialization in Kediri, analyzing whether there is an increase or decrease. The analysis tool used is: 1). Sector contribution (contribution) to the GDP, 2). Location Quotient (quotient Area), 3). Shift-Share Analysis: 4). Analysis MRP. The results of the analysis using the contributions show 1) Average sectoral contribution to the GDP the highest rates in Kediri is found in the agriculture sector and continue to decline. For the lowest contribution rate of the economic sector to the GDP at constant prices in Kediri are sectors Electricity, Gas & Water 2014 with the value of an average contribution amounting The results showed that the determination of a sector basis Basis sector is still dominated by agriculture sector and mining sector & Excavation which is as Primary Sector